2021
DOI: 10.1108/jabs-08-2020-0318
|View full text |Cite
|
Sign up to set email alerts
|

Do digital literacies matter in employee engagement in digitalised workplace?

Abstract: Purpose This study aims to understand the role of digital literacies as a moderator between employee engagement and its antecedents, namely, workplace digitalisation and innovative culture. Design/methodology/approach A total of 256 valid samples were used in the analysis. The respondents were individuals used as management-level executives in companies located in Selangor/Kuala Lumpur. The model was tested using structural equation modelling. Findings The findings reveal that there exists a significant as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…The last finding of this study which is related to H2 also reveals the significant effect of work environment on employee retention in the Malaysian service industry, thus confirming those of previous studies by Hee and Rhung ( 2019 ); Ni et al ( 2020 ); Chan et al ( 2021 ). A positive work environment is one of the most important factors influencing employee retention.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The last finding of this study which is related to H2 also reveals the significant effect of work environment on employee retention in the Malaysian service industry, thus confirming those of previous studies by Hee and Rhung ( 2019 ); Ni et al ( 2020 ); Chan et al ( 2021 ). A positive work environment is one of the most important factors influencing employee retention.…”
Section: Discussionsupporting
confidence: 90%
“…Suifan et al ( 2018 ) found that supervisory support is significant in physically expressing and signaling a supportive work environment in a company. Employees are also likely to be more engaged in their work when an organization provides new technology and tools to improve the working environment (Feige, 2019 ; Chan et al, 2021 ). Therefore, the current study hypothesized that:…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Digitalisation is radically transforming job design, job resources, professional and economic activities all over the world, which warrant continuous exploration of how workplace digitalisation influences employees' engagement (Chan et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Digitalisation is radically transforming job design, job resources, professional and economic activities all over the world, which warrant continuous exploration of how workplace digitalisation influences employees' engagement (Chan et al, 2021). Digitalisation is the application of digital technologies and infrastructures in business, economy and society (Autio, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The consideration of soft factors under the influence of digital technologies has been investigated in the management level (Antonizzi and Smuts, 2020; Mugge et al , 2020; Purba, 2021), customer and supplier level (Buer et al , 2021; Grandinetti et al , 2020; Rossini et al , 2021), employee level (Albukhitan, 2020; Mokudai et al , 2021; Raweewan and Kojima, 2020) and quality and environmental level (Llopis-Albert et al , 2021; Mugge et al , 2020; Raweewan and Kojima, 2020). The impact of digital transformation on employee behaviours has also been discussed on intra-role behaviours level (Chan et al , 2021; Dutta et al , 2020; Martínez-Caro et al , 2020), extra-role behaviours level (Haipeter, 2020; Jones et al , 2021; Kim and Park, 2021) and at the personal development and growth level (Choi et al , 2020; Lei et al , 2020; Wang and Han, 2020).…”
Section: Introductionmentioning
confidence: 99%